A mechanism to initiate emergency type 2 myelopoiesis - Alexandre Fagnan; Cristina Di Genua; Yiran Meng; Roy Drissen; Zishan Zhang; Bowen Zhang; Padraic G. Fallon; Vassilis Pachnis; Erika J. Mancini; Fränze Progatzky; Claus Nerlov (Nature, 2026)
Abstract Immune responses to parasite infection involve the increased production of basophils and eosinophils. These two myeloid cell types have key roles in type 2 anti-parasite immunity 1 and rely on GATA family transcription factors for their specification 2,3 . The first committed step in basophil and eosinophil production is generation of basophil–eosinophil–mast cell progenitors (BEMPs) from oligopotent erythroid-primed multipotent progenitors (EMPPs). However, it is not well established how immune responses act on progenitors to initiate type 2 myelopoiesis. Here we show that infection with the helminth Heligmosomoides polygyrus increases EMPP commitment to myeloid fate at the expense of erythropoiesis. Upon infection with H. polygyrus , the IL-33 alarmin accumulated in the bone marrow, causing EMPPs to upregulate the GATA co-factor LMO4 and preferentially differentiate into myeloid cells. LMO4 was sufficient to instruct myeloid fate in EMPPs by interacting with GATA2, displacing the FOG1 co-factor and redistributing GATA binding from megakaryocyte–erythroid-specific to basophil, eosinophil and mast cell (BEM)-specific chromatin. Accordingly, mice carrying a GATA2 mutation that selectively impairs the LMO4–GATA2 interaction were deficient in GATA factor allocation to BEM chromatin, myeloid lineage commitment, basophil and eosinophil production, and parasite control. This identifies LMO4 as an IL-33-regulated master regulator of type 2 myelopoiesis, and transcription factor reallocation as a mechanism of lineage commitment.